Maine’s Public Reserved Lands: A Tale of Loss and Recovery - Barringer, Richard; Schepps, Lee; Urquhart, Thomas; Wilk, Martin (Maine Policy Review, 2020)
The story of Maine’s public reserved lands—or public lots—is worth the telling for its own sake and for its enduring lessons. Provided for in the Maine Constitution of 1820 and neglected for more than a century, the public lots were once scattered widely across the Unorganized Territory of northern, western, and eastern Maine. Today, they are restored to public use and benefit, reassembled into large blocks of land that, in aggregate, are more than twice the size of Baxter State Park. These consolidated public lots offer a wide spectrum of extraordinary values, include many of the crown jewels of Maine’s natural heritage, and will remain for public use and enjoyment as long as they are valued, accessed, and safeguarded from harm.